PENGEMBANGAN INSTRUMEN ASESMEN UNTUK MENDETEKSI PENGALAMAN TRAUMATIS PENYINTAS ERUPSI GUNUNG BERAPI - Salma, Salma; Hidayat, Rahmat (Faculty of Psychology, Diponegoro University, 2016)
Volcano eruption was one kind of disaster which could cause psychological problems among its survivors. Traumatic experience particularly was one of three determinant factors which increases risk of psychological problems after disaster. Hence, a rapid assessment instrument of survivors’ traumatic experience could examine vulnerability of survivors, so that an effective intervention could be done for them. The study aims to develop rapid assessment instrument for Merapi eruption survivors namely Traumatic Experience’s Checklist. Concurrent validity of the instrument is tested for trauma which is known as one of the most common psychological problems after disaster. A number of 66 survivors participated in this study with age above 21 years old. Subjects were divided into three zones: victim, endangered, and evacuated zone. Data were collected using Traumatic Experience’s Checklist for measuring traumatic experience and Harvard Trauma Questionnaire (HTQ) for measuring trauma. Pearson’s product moment analysis was used in the study analysis. The result showed that the instrument is valid and has significant positive correlation with trauma (r= .487; p< .001). Zonation also showed a significant ability to differentiate the level of trauma among survivors. Further discussion and study is needed to find the best rapid assessment method to predict psychological problems among volcano eruption survivors.